2019
DOI: 10.3748/wjg.v25.i38.5732
|View full text |Cite
|
Sign up to set email alerts
|

Role of ion channels in gastrointestinal cancer

Abstract: In their seminal papers Hanahan and Weinberg described oncogenic processes a normal cell undergoes to be transformed into a cancer cell. The functions of ion channels in the gastrointestinal (GI) tract influence a variety of cellular processes, many of which overlap with these hallmarks of cancer. In this review we focus on the roles of the calcium (Ca2+), sodium (Na+), potassium (K+), chloride (Cl-) and zinc (Zn2+) transporters in GI cancer, with a special emphasis on the roles of the KCNQ1 K+ channel and CFT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
111
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(115 citation statements)
references
References 355 publications
(440 reference statements)
4
111
0
Order By: Relevance
“…However, the detailed regulation mechanisms are still poorly understood. Intracellular Ca 2+ plays important roles in the regulation of a variety of cellular processes, such as cell cycle, apoptosis, and migration [21] [22]. Recent studies have shown that inositol trisphosphate receptor type 1 (IP 3 R 1 )-mediated Ca 2+ release increases the cytosolic free Ca 2+ level, which induces miscarriage in rat [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, the detailed regulation mechanisms are still poorly understood. Intracellular Ca 2+ plays important roles in the regulation of a variety of cellular processes, such as cell cycle, apoptosis, and migration [21] [22]. Recent studies have shown that inositol trisphosphate receptor type 1 (IP 3 R 1 )-mediated Ca 2+ release increases the cytosolic free Ca 2+ level, which induces miscarriage in rat [23].…”
Section: Discussionmentioning
confidence: 99%
“…Although the occurrence and progression of cancer are complex, numerous findings indicate that aberrant intracellular Ca 2+ ([Ca 2+ ] i ) signaling is involved in the development of several types of gastrointestinal (GI) cancers, including GC and colon cancer [4]. Since plasma membrane Ca 2+ -permeable channels play important roles in the regulation of [Ca 2+ ] i , their aberrant expression and function are positively associated with the occurrence and development of GI tumors [5,6]. Consistently, we revealed that activation of G protein-coupled receptors (GPCRs), such as Ca 2+ sensing receptors (CaSR) and vasoactive intestinal polypeptide (VIP) receptors, promotes GC progression via transient receptor potential vanilloid receptor 4 (TRPV4) channels and the Ca 2+ signaling [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…These include multiple signal transduction and downstream signaling events, including regulation of gene expression, secretion of enzymes and hormones, and intracellular communication between compartments (Chen et al, 1994;Tolon et al, 1996;Stock and Schwab, 2015). A stable regulation of these processes maintains normal tissue homeostasis, such as cell cycle progression, migration, and apoptosis (Kunzelmann, 2005;Kunzelmann, 2016;Prevarskaya et al, 2018;Anderson et al, 2019). Accordingly, dysregulated expression as well as altered function of ion channels are related to a great number of diseases (Kim, 2014), and can drive the transformation from normal to malignant cell behavior (Litan and Langhans, 2015).…”
Section: Introductionmentioning
confidence: 99%